Green Meeting Implementation at The Apurva Kempinski Bali - Ahmad Riri Nurany; I Ketut Sutama; I Gede Mudana; Ni Gusti Nyoman Suci Murni (International Journal of Green Tourism Research and Applications, 2021)
This study aims to maximize the implementation of two aspects, namely the Green Meeting Concept with Green MICE Business. The study uses qualitative descriptive analysis techniques by exploring the explanation of the green economy concept, things that affect the green economy, the benefits of green MICE Business and supporting government policies. As to overcome this problem, the event organizers should limit the number of waste used in an event. Therefore, it is important that event handlers practice environmental protection during organizing an event. Evaluating environmental impacts from both positive and negative perspectives provides a better understanding of the proper use of natural resources. Perform calculations for investment planning to support the green MICE movement as part of supporting a green economy.